Le competenze valutative: un'indagine empirica su prassi e opinioni degli insegnanti del primo ciclo di istruzione della Regione Lazio - Anna Maria Ciraci (LED Edizioni Universitarie, 2019)
The article deals with the results of an empirical research on the practices and opinions of primary and middle school teachers of the Lazio Region. To collect the information, two questionnaires were administered to two samples of 233 and 103 teachers. After a first descriptive analysis, the Multiple Correspondence Analysis was used in order to identify associations between the observed variables and behavior/attitude clusters. From the data a framework emerges in which there are some new elements, such as the low use of traditional tests and the use of evaluation as a resource for learning, but which still presents some critical aspects, such as the prevalent use of testing for the assessment of skills and difficulties in the construction of adequate verification tools. The groups that have distinguished themselves for less frequent use of tools and activities, have in common the lower seniority of service and the origin from some specific territorial areas of the region.